The Effect of Teaching through Simulation of the Performance of Nurses in Neonatal Resuscitation in Farideh Behbahani Hospital Iran - Marzieyeh Kargar; Zahra Bagheri; Rezvan Mahfoozi; Mostajab Razavinejad; Zahra Bagheri (Kerman University of Medical Sciences, 2016)
Background & Objective: Nursing staff can prevent asphyxia and neonatal mortality by learning the correct resuscitation principles Therefore this study was performed with the aim to determine the effectiveness of teaching through simulation and filming of the performance of nurses in neonatal resuscitation Methods: In this experimental study 40 nursing staff were divided into teams of 2 nurses through simple randomization The level of knowledge before and after the intervention was evaluated using a written exam To assess performance before and after the intervention simulated environment and scenario building were used All stages of resuscitation of the teams were filmed Before training the experimental group participants viewed their videos and were trained through error analysis practicing on manikin and viewing educational videos of resuscitation (2011) The videos were evaluated and scored by two instructors through doubleblind techniques and using a standard checklist Data were analyzed in SPSS software using independent sample ttest paired ttest repeated measurement and Pearson correlation coefficient Results: The level of knowledge in the control and experimental groups increased by 9 and 10 scores respectively This difference was not statistically significant (P = 0830) Before the training no statistically significant difference was observed in terms of performance (P = 0109) However one month after training a significant difference was observed between the two groups in terms of performance (P < 0001) This reflects the effect of training on performance of the experimental group Conclusion: The results showed that the simultaneous use of simulation and filming for training will be more effective in the learning process Thus it is better that both techniques be used for training to be more effective